Mutagenesis development of actinoplanes sp. KCTC 9161 by N-methyl-N’-nitro-N-nitrosoguanidine (NTG) and screening for acarbose production - Tuyen, Do Thi; Duong, Nguyen The; Hoang, Le Thanh (Vietnam Journal of Biotechnology, 2018)
Acarbose has been widely used in the therapy of type II diabetes (non-insulin dependent) because it controls blood sugar contents of patients after meals. Acarbose, a pseudo-oligosaccharide, acts as a competitive -glucosidase inhibitor. Acarbose is produced by the strains of Bacillus, Streptomyces and Actinoplanes sp. The aim of this study was to develop mutagenesis for an Actinoplanes sp. strain and screening for acarbose production. The spores of Actinoplanes sp. KCTC 9161 strain were subjected to be mutated by N-methyl-N’-nitro-N-nitrosoguanidine (NTG) for screening and finding mutant strains that were capable of production of higher acarbose (an inhibitor of α-glucosidase) higher than wild type strain. Firstly, the original NTG solution was prepared in phosphate buffer 0.05 M, pH 6.9 and the safety concentration of NTG was determined at 5 mg/ml. Then, the spores were incubated with different NTG amounts and duration. The living colonies were transferred to fermentation medium. The results obtained showed that 15 mutant strains were produced higher acarbose than wild type when used thin layer chromatography method for analysis and comparing with standard acarbose (Sigma). Three cell lines among total tested 15 mutant lines of Actinoplanes sp. KCTC 9161 produced acarbose at a higher level or indicated a higher inhibitory activity toward α-glucosidase than the original strain. Enzymatic inhibitory ativity of α-glucosidase of three mutant strains (Actinoplanes sp. KCTC- L4, L11, L14) was increased 1.3 fold higher than wild type and Actinoplanes sp. KCTC spores were very sensitive to NTG toxic, 98% spores could not survive at the treatment condition of 50 µg NTG for 30 minutes. In addition, an applicable protocol for mutating Actinoplanes sp. using NTG was suggested for further research.